Evolving and Innovative Treatments for Syndesmosis Injuries: Evaluating Current Practices. Issue 3 (14th September 2018) - Hunt, Kenneth; Moon, Daniel; Phisitkul, Phinit; McCormick, Jeremy; Amendola, Annunziato
Category: Sports Introduction/Purpose: Despite extensive research of syndesmotic fixation techniques, there is little consensus regarding optimal treatment and return to play protocols for isolated syndesmotic injuries. As competing treatment goals may exist, orthopedic clinicians have resorted to a wide variety of treatment strategies, ranging from screw fixation to suture fixation in various constructs. Given the myriad techniques and constructs, it is increasingly important to understand the rationale and intended patient setting for selecting particular implants and constructs. Undoubtedly, a multitude of factors contribute to the range of outcomes following syndesmotic fixation. While there are various theoretical arguments made for selecting one construct over another, this study seeks to assess the distribution of current practice approaches to syndesmotic injuries by foot and ankle orthopaedic surgeons at large. Methods: This cross-sectional study collected data from trained, licensed orthopedic surgeons (i.e. MD, DO, etc.) practicing in North America that treat isolated syndesmotic injuries. A one-time online survey was disseminated to the AOFAS membership. The survey contained questions regarding participant demographics, indications for treating syndesmotic injuries, preferred technique for repairing the syndesmosis and post-operative management, as applied to six athlete scenarios (moderate, high, and very high impact athletes with complete syndesmosis injury, with and without complete deltoid injury), and post-operative return to play protocols. Frequencies and percentages were calculated for all categorical responses using STATA 14.2. Free text responses were analyzed for common themes by fellowship trained, licensed orthopedic surgeons. Results: 273 of 337 responses were complete. Radiographic widening of greater than 2 mm at the syndesmosis was a sole indication for surgery for 83% of respondents, and arthroscopic widening of the syndesmosis was a sole indication for 75%. No clinical exam or MRI finding reached a threshold of 50% as a sole indication. In moderate and high-impact athletes with complete syndesmotic injury, the majority of respondents use one or two flexible fixation devices (61.5% and 50.5%, respectively), 25% use screws only, and 23.7% use a combination. More than 70% do not change their treatment construct choice in the presence of a complete deltoid injury. There was considerable variability in anticipated return to sport amongst respondents for all injury scenarios, ranging from 2 weeks to 6 months. Conclusion: There is a wide variety of indications and treatment constructs employed by orthopaedic surgeons for athletes with ligamentous syndesmotic injuries requiring fixation. Despite absent consensus, several trends were evident. Flexible devices were utilized by a majority of respondents in all scenarios, even with 'very high impact' scenarios. Hybrid constructs are also common. The presence of a complete deltoid injury impacted fixation constructs for very few respondents. There is substantial variability in expected return to play for all athlete and injury scenarios. The diversity of approaches highlights the need for evidence-based guidelines regarding management of syndesmotic injuries.